BUILDING BRIDGES THROUGH PLAY: A GAME DESIGN APPROACH TO ENHANCING PARENT- YOUNG ADULT COMMUNICATION. - Madan, Teesha; Bhattacharjee, Sandipan; Saha, Bhaskar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the intricate landscape of family dynamics, cultivating transparent communication between parents and young adults poses a nuanced challenge. This research delves into the development and impact of a distinctive game designed to transmute awkward conversations into potent instruments for fortifying connections between these two groups. The central objective of this game is to forge a secure and captivating space that nurtures open dialogue, enabling both parents and young adults to exchange personal narratives and experiences. The ultimate goal is to cultivate an environment where young adults feel at ease initiating discussions with their parents. Employing a dual survey method — a questionnaire and a prototype — substantiated the necessity for an intervention and validated the game design concept. Grounded in the belief that awkward conversations can catalyse more meaningful communication, the game offers a structured platform for instances when a young adult grapples with expressing themselves or when parents sense a detachment from their child’s life. The iterative nature of the game, featuring multiple rounds, ensures reciprocity in sharing stories, fostering a balanced and open dialogue. This innovative approach seeks to dismantle communication barriers and foster empathy, contributing to the realm of game design by highlighting the potential of interactive experiences in facilitating significant conversations within families.